BRICS and the Politics of Multi-Polarity: Rethinking Global Governance - Anagba, Joseph Obidi; Adamu , Bitrus Matawal; Olotu , Timilehin Ibrahim (Journal of Contemporary International Relations and Diplomacy, 2026)
The BRICS countries (Brazil, Russia, India, China, and South Africa), and its recent expansion, has evolved beyond its economic foundations to emerge as a formidable actor influencing global governance. This article critiqued portrayals of BRICS as a merely symbolic or disjointed alliance, arguing that it offers a viable alternative to the Western-dominated global order. It challenges the representativeness of traditional institutions like the UN, IMF, and World Bank, while examining BRICS’ initiatives such as the New Development Bank and de-dollarisation efforts. Being a qualitative research, secondary data was utilized to analyze BRICS’ institutional strategies, ideological narratives, and policy tools that seek to reshape global power configurations. The study is anchored on two theories, the Neo-Gramscian and Structural Realism. The study argued that BRICS functions both as a symbol and agent of multi-polarity and examines whether the coalition can consolidate a coherent global vision beyond being a protest bloc. The study established in its findings that, BRICS is the alternative to Western dominated global institutions, thus, providing a change in the unipolar grips on global politics. One of the recommendations given is that as an alternative to unipolarity, BRICS should promote South-South alliances so as to strengthen its New Development Bank that will measure up with the global institutions such as the World Bank and IMF. Its evolving role may be pivotal to the future of global governance.